A Fuzzy Credibility Constrained Programming Approach for Agricultural Water Resources Management - He, Li; Song, Xin Shuang; Lu, Hong Wei; Li, Xiao Meng (Applied Mechanics and Materials, 2014)
In this study, a fuzzy credibility constrained programming (FCCP) model is developed for agricultural irrigation systems management under uncertainty. It is then applied to a real case study in a depression at southern Urumqi, China. The optimization model can be adjusted according to various considerations from decision makers, and thus much optimal and applicable management strategies can be expected through identifying the most appropriate credibility level for the system.